Plasmonic Optoelectronic Memristor Enabling Fully Light‐Modulated Synaptic Plasticity for Neuromorphic Vision. Issue 6 (29th December 2021) - Shan, Xuanyu; Zhao, Chenyi; Wang, Xinnong; Wang, Zhongqiang; Fu, Shencheng; Lin, Ya; Zeng, Tao; Zhao, Xiaoning; Xu, Haiyang; Zhang, Xintong; Liu, Yichun
Abstract: Exploration of optoelectronic memristors with the capability to combine sensing and processing functions is required to promote development of efficient neuromorphic vision. In this work, the authors develop a plasmonic optoelectronic memristor that relies on the effects of localized surface plasmon resonance (LSPR) and optical excitation in an Ag–TiO2 nanocomposite film. Fully light‐induced synaptic plasticity (e.g., potentiation and depression) under visible and ultraviolet light stimulations is demonstrated, which enables the functional combination of visual sensing and low‐level image pre‐processing (including contrast enhancement and noise reduction) in a single device. Furthermore, the light‐gated and electrically‐driven synaptic plasticity can be performed in the same device, in which the spike‐timing‐dependent plasticity (STDP) learning functions can be reversibly modulated by visible and ultraviolet light illuminations. Thereby, the high‐level image processing function, i.e., image recognition, can also be performed in this memristor, whose recognition rate and accuracy are obviously enhanced as a result of image pre‐processing and light‐gated STDP enhancement. Experimental analysis shows that the memristive switching mechanism under optical stimulation can be attributed to the oxidation/reduction of Ag nanoparticles due to the effects of LSPR and optical excitation. The authors' work proposes a new type of plasmonic optoelectronic memristor with fully light‐modulated capability that may promote the future development of efficient neuromorphic vision. Abstract : A novel plasmonic optoelectronic memristor is demonstrated for the first time relying on localized surface plasmon resonance (LSPR) effect. Both fully light‐modulated and light‐gated electrically‐driven synaptic modulation can be implemented in such a single device. Furthermore, combination of visual sensing, low‐level (contrast enhancement and noise reduction), and high‐level image processing (image recognition) promotes the development of efficient neuromorphic vision.